Seasonal Changes in the Biochemical Composition of Ovary in Hetero pheustes fossilis ( bloch) - SHRENI, KALPANA D (Fishery Technology, 2017)
Seasonal changes in the biochemical composition of ovary in H. fossilis are reported. An inverse relationship was noted in fat and water contents. Maximum fat was observed in June and lowest in December. Protein and ash were generally low during winter and high during summer or monsoon months. Variations in the cholesterol content were more or less identical to those of the fat.